Salt stress induces SFT expression to promote early flowering and inhibits floral organ development by disturbing cell cycle in tomato - Fengze Sun; Yahui Wang; Genzhong Liu; Dong Fang; Mingxuan Sun; Zhilong Bao; Fangfang Ma (Vegetable Research)
Excessive application of fertilizers and continuous cropping result in a large amount of salt residues remaining in the soil, leading to salt stress in the following crop cultivation. Salt stress jeopardizes the growth and development of plants and poses a great challenge to tomato production. Floral transition is a critical step in determining the crop yield. Here the impact of salt stress on tomato (Solanum lycopersicum) floral transition using various concentrations of NaCl solutions is investigated. Salt stress significantly reduced plant biomass compared to the control. We observed an early flowering phenotype and smaller flowers in tomato plants treated with 50−150 mM NaCl solution relative to the control. RT-qPCR analyses of genes involved in floral transition revealed that the SFT gene was upregulated under salt stress suggesting the activation of SFT (SINGLE-FLOWER TRUSS)-AP1(APETALA 1) pathway-mediated floral transition. Salt treatment led to a decrease in tomato seedlings biomass, particularly in floral organs. Meanwhile, plants treated with 150 Mm NaCl also produced much smaller fruits than the control leading to a significant decrease in yield. Nuclear DNA ploidy analysis of various floral tissues in tomato has revealed significant impacts of salt stress on the intranuclear replication within sepals and petals. We indicate that the cell cycle in floral organs is disrupted by salt stress, primarily through its influence on the transcription of CycA2;1 and CycB1;2. Our study elucidates that salt stress promotes early flowering by inducing SFT expression and retard tomato floral organ development via perturbation of the cell cycle.